Managing investment potential for the development of small enterprises - Mammadova, K.; Ahmadova, L.; Guliyev, F.; Маммадова, К. М.; Ахмадова, Л. Б.; Гулієв, Ф. Н. (Харківський національний автомобільно-дорожній університет, 2026)
Small enterprises constitute a fundamental segment of national and regional economies, driving job creation, innovation, and GDP growth. Despite their strategic importance, these enterprises frequently face constraints in accessing capital, managing investment risks, and fully exploiting their investment potential. This study investigates the management of investment potential in small enterprises, emphasizing a holistic, multidimensional approach that integrates financial, managerial, technological, and sustainability dimensions. Drawing on theoretical frameworks, international best practices, and practical implementation strategies, the research develops a conceptual model linking internal resources, external environmental factors, strategic management processes, and adaptive feedback mechanisms. The framework highlights the dynamic interaction between financial capacity, managerial competencies, technological readiness, innovation capability, market conditions, regulatory quality, and ESG compliance. It further incorporates scenario analysis, risk mitigation, capital allocation, performance monitoring, and continuous learning to enhance enterprise resilience and sustainable growth. Special attention is given tocontextual adaptation within emerging economies, exemplified by Azerbaijan, where institutional constraints, market volatility, and limited managerial capacities pose additional challenges. The study demonstrates that effective investment potential management requires not only access to financial resources but also the development of human capital, adoption of innovative technologies, alignment with strategic objectives, and adherence to international standards. By operationalizing these mechanisms within a unified conceptual framework, small enterprises can transform investment potential into tangible outcomes, strengthen competitiveness, and achieve sustainable development in dynamic and uncertain environments. The proposed model provides a practical roadmap for researchers and practitioners seeking to optimize investment strategies and enhance the long-term viability of small enterprises.
Управління інвестиційним потенціалом для розвитку малих підприємств
Keywords: 332.12: 334.72; 10.30977/ЕТК.2225-2304.2026.47.261